1997
DOI: 10.1021/ja9626345
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism in Molecular Crystals:  Stabilization of a Metastable Form by Conformational Mimicry

Abstract: A combined modeling and experimental strategy has been applied to the problem of stabilisation of a metastable conformational polymorph. For the first time additives have been successfully selected which by virtue of their conformation are able to selectively inhibit the appearance of the stable β polymorph of l-glutamic acid and hence stabilize the metastable α structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
299
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 331 publications
(305 citation statements)
references
References 20 publications
4
299
1
1
Order By: Relevance
“…3,[8][9][10][11][12] Generally, crystallisation additives are effective in producing polymorphs of pharmaceuticals while avoiding others by encouraging the growth of a desirable form or disrupting the growth of the other form. 8,9,13,14 Modification of crystal shape occurs as the polymer deposition on the crystal surface inhibits the growth of specific surfaces of the crystal. 13 Reduction of particle size by means of long molecular weight additives was only marginally reported in the literature, and exception is perhaps the work of Femi-Oyewo and , although a recent work by Xie et al 12 showed that salbutamol sulphate crystal size was reduced to less than 10 µm upon presence of polymer additives HPMC, polyvinylpyrrolidone (PVP K25), lecithin and Span 85 during anti-solvent water-ethanol crystallisation.…”
Section: Introductionmentioning
confidence: 99%
“…3,[8][9][10][11][12] Generally, crystallisation additives are effective in producing polymorphs of pharmaceuticals while avoiding others by encouraging the growth of a desirable form or disrupting the growth of the other form. 8,9,13,14 Modification of crystal shape occurs as the polymer deposition on the crystal surface inhibits the growth of specific surfaces of the crystal. 13 Reduction of particle size by means of long molecular weight additives was only marginally reported in the literature, and exception is perhaps the work of Femi-Oyewo and , although a recent work by Xie et al 12 showed that salbutamol sulphate crystal size was reduced to less than 10 µm upon presence of polymer additives HPMC, polyvinylpyrrolidone (PVP K25), lecithin and Span 85 during anti-solvent water-ethanol crystallisation.…”
Section: Introductionmentioning
confidence: 99%
“…LGA has two recognized polymorphic forms: the metastable, more soluble and prismatic -form, and the stable, less soluble and needle-like -form [20]. A high-resolution analytical balance (made by Mettler-Toledo) with precision of one ten thousandth was used to weigh the LGA samples for experiment.…”
Section: Methodsmentioning
confidence: 99%
“…The L-GA crystals are known to have two polymorphs (Davey et al, 1997;Kitamura and Ishizu, 2000), the prismatic  and the needle-like  forms. (1)…”
Section: Methodsmentioning
confidence: 99%